Transcriptome Analysis of Scrippsiella trochoidea CCMP 3099 Reveals Physiological Changes Related to Nitrate Depletion - Cooper, Joshua T.; Sinclair, Geoffrey A.; Wawrik, Boris (Frontiers in Microbiology, 2016)
Dinoflagellates are a major component of marine phytoplankton and many species are recognized for their ability to produce harmful algal blooms (HABs). Scrippsiella trochoidea is a non-toxic, marine dinoflagellate that can be found in both cold and tropic waters where it is known to produce “red tide” events. Little is known about the genomic makeup of S. trochoidea and a transcriptome study was conducted to shed light on the biochemical and physiological adaptations related to nutrient depletion. Cultures were grown under N and P limiting conditions and transcriptomes were generated via RNAseq technology. De novo assembly reconstructed 107,415 putative transcripts of which only 41% could be annotated. No significant transcriptomic response was observed in response to initial P depletion, however, a strong transcriptional response to N depletion was detected. Among the down-regulated pathways were those for glutamine/glutamate metabolism as well as urea and nitrate/nitrite transporters. Transcripts for ammonia transporters displayed both up- and down-regulation, perhaps related to a shift to higher affinity transporters. Genes for the utilization of DON compounds were up-regulated. These included transcripts for amino acids transporters, polyamine oxidase, and extracellular proteinase and peptidases. N depletion also triggered down regulation of transcripts related to the production of Photosystems I & II and related proteins. These data are consistent with a metabolic strategy that conserves N, while maximizing sustained metabolism by emphasizing the relative contribution of organic N sources. Surprisingly, the transcriptome also contained transcripts potentially related to secondary metabolite production, including a homolog to the Short Isoform Saxitoxin gene (sxtA) from Alexandrium fundyense, which was significantly up-regulated under N-depletion. A total of 113 unique hits to Sxt genes, covering 17 of the 34 genes found in C. raciborskii were detected, indicating that S. trochoidea has previously unrecognized potential for the production of secondary metabolites with potential toxicity.